We Should Not Get Rid of Incivility Online. (July 2019) - Masullo Chen, Gina; Muddiman, Ashley; Wilner, Tamar; Pariser, Eli; Stroud, Natalie Jomini
Incivility and toxicity have become concepts du jour in research about social media. The clear normative implication in much of this research is that incivility is bad and should be eliminated. Extensive research—including some that we've authored—has been dedicated to finding ways to reduce or eliminate incivility from online discussion spaces. In our work as part of the Civic Signals Initiative, we've been thinking carefully about what metrics should be adopted by social media platforms eager to create better spaces for their users. When we tell people about this project, removing incivility from the platforms frequently comes up as a suggested metric. In thinking about incivility, however, we've become less convinced that it is desirable, or even possible, for social media platforms to remove all uncivil content. In this short essay, we discuss research on incivility, our rationale for a more complicated normative stance regarding incivility, and what other orientations may be more useful. We conclude with a post mortem arguing that we should not abandon research on incivility altogether, but we should recognize the limitations of a concept that is difficult to universalize.